EFEKTIVITAS MODEL CTL DAN MODEL PBL TERHADAP HASIL BELAJAR IPS - Ari Wijayanti; Taat Wulandari (Program Pascasarjana Universitas Negeri Yogyakarta, 2016)
Penelitian ini mengetahui perbedaan hasil belajar siswa yang menggunakan model PBL dan model CTL; serta membedakan efektivitas antara model CTL dan model PBL untuk meningkatkan hasil belajar IPS di SMPN 2 Bantul. Jenis penelitian adalah quasi experiment dengan subject match design. Populasi penelitian seluruh siswa kelas VIII SMPN 2 Bantul yang berjumlah 6 kelas. Sampel dipilih sebanyak dua kelas menggunakan teknik simple random sampling. Kelas VIII B sebagai kelompok eksperimen 1 (CTL), dan kelas VIII C sebagai kelompok eksperimen 2 (PBL). Teknik pengumpulan data menggunakan tes. Teknik analisis data menggunakan independent sample t-test, dilanjutkan dengan effect size. Hasil penelitian terdapat perbedaan peningkatan hasil belajar yang signifikan antara siswa yang belajar dengan model PBL dan model CTL. Model PBL lebih efektif daripada model CTL untuk meningkatkan hasil belajar IPS. Dapat dilihat dari effect size model PBL sebesar 3,02 lebih tinggi daripada effect size model CTL sebesar 2,02. THE EFFECTIVENESS OF THE CTL MODEL AND PBL MODEL ON THELEARNING ACHIEVEMENT IN THE SOCIAL STUDIESAbstractThis study aims to know the significant difference of the learning achievement improvement between students who are taught by using the PBL model and that of those taught by using the CTL model, and the effectiveness between CTL and PBL models on the learning achievement in the Social Studies of the students of SMPN 2 Bantul. This research is a quasi experiment with the match subject design. The population is all of 8 grade students of SMPN 2 Bantul. The sample was selected from two classes by using the random sampling technique. The first group was class VIII B (CTL), and the second group was class VIII C (PBL). The data collecting technique used was a test. The data analysis used the independent sample t-test, followed by the effect size.The result of this research shows that there is a significant difference of the learning achievement improvement between the students who were taught by using the PBL model and that of those taught by using the CTL model. It means the PBL model is more effective than the CTL model in improving the learning achievement in the Social Studies. It can be seen from the effect size of the PBL model 3.02 which is higher than that of the CTL model, that is 2.02.